2018
DOI: 10.1007/s00253-018-9175-2
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl disulfide from garlic oil inhibits Pseudomonas aeruginosa virulence factors by inactivating key quorum sensing genes

Abstract: Garlic oil can disrupt the quorum sensing (QS) pathways of the opportunistic pathogen Pseudomonas aeruginosa; however, the underlying mechanisms for this effect are unclear. Diallyl disulfide (DADS) is one of the most abundant sulfur-containing compounds in garlic oil. This study investigated the effects of DADS on the growth, virulence factor production (elastase, pyocyanin, biofilm, and swarming motility), and essential gene expression of P. aeruginosa PAO1, particularly as they apply to QS and virulence. DA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…Bacteria have a barrier system, biofilm formation, which inhibits the entry of disinfectants, antibiotics and host immune molecules into the bacterial cells and is a major cause of the drug-resistance of bacteria (44). In addition, QS molecules, such as AHL regulate biofilm formation, intercellular communication, bacterial population and other processes (3,4,11,46). The inhibition of biofilm formation and QS has been studied in various scientific and technological fields.…”
Section: Effects Of Sulfur Compounds On Biofilm Formation and Quorum mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria have a barrier system, biofilm formation, which inhibits the entry of disinfectants, antibiotics and host immune molecules into the bacterial cells and is a major cause of the drug-resistance of bacteria (44). In addition, QS molecules, such as AHL regulate biofilm formation, intercellular communication, bacterial population and other processes (3,4,11,46). The inhibition of biofilm formation and QS has been studied in various scientific and technological fields.…”
Section: Effects Of Sulfur Compounds On Biofilm Formation and Quorum mentioning
confidence: 99%
“…Therefore, it is difficult for allicin to reach the infected sites of the body as an intact form. Recent studies have demonstrated that sulfur-containing compounds derived from garlic, such as diallyl disulfide (DAS 2 ) and ajoene, inhibit biofilm formation and the QS of bacteria, even though the antimicrobial activities of these compounds are lower than those in medical antibiotics used in clinical settings (11)(12)(13)(14)(15)(16). Furthermore, Slachmuylders et al and others have demonstrated that some natural products, which exert an inhibitory effect on biofilm formation, have antibiotic-potentiating activity (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DADS down-regulated several important genes ( lasI , lasR , rhlI , rhlR , pqsA , and pqsR ) of the las , rhl , and pqs QS systems. Therefore, we concluded that DADS inhibits P. aeruginosa PAO1 pathogenic factors by inactivating the key genes of las , rhl , and pqs QS systems (Li et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Pseudomonas aeruginosa is a ubiquitous, clinically significant, Gram-negative bacillus and an opportunistic human pathogen (Stover et al, 2000; Lee et al, 2018). P. aeruginosa infections are particularly difficult to eradicate because this pathogen is prone to acquire resistance to multiple antibiotics and it prefers to form antibiotic-resistant biofilms (Galloway et al, 2012; He et al, 2018; Li et al, 2018). In recent years, a number of studies have reported that garlic extract contains P. aeruginosa QS inhibitors, including ajoene, a sulfur compound from garlic (Rasmussen et al, 2005; Bodini et al, 2009; Harjai et al, 2010; Jakobsen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation